Rheological properties of mucin from the snail Achatina fulica - Ovcharuk, Maryana; Topchiy, Oksana (My University, 2025)
This article examines the functional role of various thickeners in cosmetic formulations. The study of their rheological properties and behaviour in aqueous solutions is essential for the development of stable and effective products within the skincare and dermocosmetic sectors. This study aimed to investigate the behaviour of a novel, naturally derived cosmetic ingredient – mucin from the snail Achatina fulica – in an aqueous medium under varying pH conditions, and to provide practical recommendations for its use. The study included an analysis of the physicochemical properties, mechanisms of action, and functional characteristics of five key thickeners: guar gum, Aristoflex, sodium alginate, gelatine, and carbomer. Their technological advantages, limitations, and applications in cosmetic products were outlined. In an aqueous solution, mucin exhibited a high swelling capacity: within 90 minutes, its volume increased ninefold, which is comparable to the performance of other hydrocolloids examined. The structural viscosity of mucin solutions within the concentration range of 0.1%-10.0% is characterised by a non-linear increase. A marked rise in viscosity is observed at concentrations between 1.5% and 3.0%, which is attributed to the attainment of maximum intermolecular interaction strength. It was found that the viscoelastic properties of aqueous mucin solutions depend not only on concentration but also on the pH of the medium, with mucin exhibiting non-Newtonian behaviour. Maximum structural stability was observed within the pH range of 5.0 to 6.5, where the structural viscosity of a 3.0% solution reached 127 mPa · s. Recommendations have been proposed regarding the inclusion of snail mucin in cosmetic formulations, taking into account the rheological and sensory characteristics of the final product. These insights may prove valuable to researchers and practitioners in the cosmetics industry.
Keywords: кафедра технології м’яса і м’ясних продуктів; муцин; загусник (косметика); mucin; thickener (cosmetics)